On sandwich theorems for some classes of analytic functions - T. N. Shanmugam; S. Sivasubramanian; H. Silverman (International Journal of Mathematics and Mathematical Sciences)
The purpose of this present paper is to derive some subordination and superordination results for certain normalized analytic functions in the open unit disk. Relevant connections of the results, which are presented in the paper, with various known results are also considered.